2000
DOI: 10.3928/0191-3913-20000701-09
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms and Visual Outcome in Patients With Presumed Congenital Cataract

Abstract: Purpose: To investigate clinical symptoms and visual outcome in patients who had presumed congenital cataract with visual acuity ≥20/200. Methods: Twenty-nine patients (50 eyes) ranging in age from 5-28 years were included in this study. Congenital cataract was diagnosed by patients' past history, previous medical records, and typical findings of congenital cataract. Inclusion criteria were patients with visual acuity measured by Snellen chart, best corrected visual acuity ≥20/200, and no eye or syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The most common morphological variant of cataract in our series was zonular cataract, whereas studies from Iran and South Korea have found posterior subcapsular cataract and nuclear cataract as the most common types, respectively. [ 5 11 ] Young children with early onset severe vision impairment can experience delayed motor, language, emotional, social, and cognitive development, with lifelong consequences. Because the visual acuity in children would be dependent on the child’s attention span and cooperation, we chose to use postoperative refraction (objective measurement) at a 2-year follow-up as our outcome parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The most common morphological variant of cataract in our series was zonular cataract, whereas studies from Iran and South Korea have found posterior subcapsular cataract and nuclear cataract as the most common types, respectively. [ 5 11 ] Young children with early onset severe vision impairment can experience delayed motor, language, emotional, social, and cognitive development, with lifelong consequences. Because the visual acuity in children would be dependent on the child’s attention span and cooperation, we chose to use postoperative refraction (objective measurement) at a 2-year follow-up as our outcome parameter.…”
Section: Discussionmentioning
confidence: 99%